Patterns of Dyslipidemia among Patients with Non-Alcoholic Fatty Liver Disease: Dyslipidemia among Patients with NAFLD - Shaikh, Kaleem Ullah; Kareem, Shahid; Sarfaraz, Abeer; Anwar, Muhammad Wasiq; Batool, Nida; Bakar, Saadia Abu (Pakistan Journal of Health Sciences, 2025)
Non-alcoholic fatty liver disease (NAFLD) affects a significant proportion and is frequently associated with dyslipidemia and metabolic disorders. Objective: To explore the patterns of dyslipidemia among patients with NAFLD and their association with disease severity. Methods: A cross-sectional study was conducted at the Department of Cardiology, Liaquat National Hospital, Karachi. All participants diagnosed with NAFLD were included, and NAFLD severity was assessed using Fibro Scan, categorizing patients into no significant fibrosis, mild fibrosis, significant fibrosis, and advanced fibrosis. Dyslipidemia patterns were evaluated based on lipid profiles. Results: The cohort (n=300) had a mean age of 51.44 years, with a majority being female (60.3%) and over 45 years old (71.3%). NAFLD severity was distributed as follows: 33% mild fibrosis, 32% no significant fibrosis, 29.3% significant fibrosis, and 5.7% advanced fibrosis. As NAFLD severity increased, waist circumference, liver enzyme levels (AST and ALT), and lipid markers (TC, LDL-C, TG) increased, while HDL-C decreased. Advanced cases showed higher hemoglobin A1c levels and increased hepatic steatosis and CAP values. Dyslipidemia associated with metabolic syndrome (24%), low HDL-C (61.3%), and hypertriglyceridemia (2%) were observed, with combined and general hyperlipidemia affecting 3.7% and 1.3% of participants, respectively. The patterns of dyslipidemia varied with severity; normolipidemia was common in cases with no significant fibrosis, combined hyperlipidemia was seen in significant fibrosis, and hyperlipidemia was exclusive to advanced NAFLD. Conclusion: It was concluded that the study found significant associations between NAFLD severity and dyslipidemia patterns.